Varieties and in vitro seed production technique for growing potato (Solanum tuberosum L.) under harsh and problematic BRIS soil of Pahang - Nodin, Mohd Shukor; Zakaria, Nor hafizah (Universiti Teknologi Malaysia, 2015)
Malaysia's food import bills have been enlarging steadily where food self-sufficiency is decreasing year by year. The weakness of the Malaysian agricultural sector is that it largely produces cash crops and little food. This increasing reliance for imported foods to feed the country's expanding population also has raised concern among policy makers and analysts on the long term feasibility of such policy. This concern was reflected in the previous several National Agricultural Policies and reemphasized in the current agricultural policy where increased consideration is being given to domestic production of food especially production in abandon land and marginal land like BRIS soil. BRIS soil is commonly known as a problematic soil in Malaysia. It is unsuitable for agricultural purposes as it retains a high sandy texture (>90%), low fertility, low cation exchange capacity, and low water holding capacity. However, there is a potential to grow potato under this soil as shown by various studies presented in this review. The review indicated that reasonably good yield and quality of potato can be produced under Malaysian BRIS soils if a reliable system of producing disease-free planting materials can be put in place and bacterial wilt disease can be made under control. Under those conditions, marketable tuber yields of around 19.1 ton per hectare can be achieved using clone 378597.1. Normally, potato is conventionally propagated vegetatively using seed tubers. A seed production scheme to produce disease free plantlets and microtubers in vitro is proposed. By adopting the proposed scheme, the cost of planting materials is expected to be reduced.